GOOGLE JAMBOARD ALTERNATIF MEDIA KREATIF UNTUK PEMAHAMAN TATA BAHASA PERANCIS - Al Adawiyah, Aisyiah (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
In Era Society 5.0, teachers must have expertise in using ICT to teach online during the pandemic. They also need to adapt their teaching to the characteristics of students as millennials become creative, innovative, and competitive generations. The formation effort is realized through the use of Google Jamboard as a creative medium in the Introductive Grammar course. The general purpose of using it is to encourage students to learn independently, to inspire creativity and collaboration, and to focus on the problem-solving process. Introductive Grammar is a course that has a fairly high level of difficulty to understand, so knowing the level of understanding of students in the French Education Section, Universitas Negeri Semarang is a special purpose of using this web application. This part of Classroom Action Research is organized after students had a decreased accuracy of the Final Semester Examination by 18%. We focus on improving the quality of the learning process in the classroom so that student learning outcomes can be improved provides information in creating creative content about lesson material. It turns out that their jamboards are very creative, innovative, and competitive between one student and another so that these works can be used to describe the learning of the Introductive Grammar course in the next year's academics.